2015
DOI: 10.1155/2015/609194
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Dysfunction in Patients Experiencing Cardiotoxicity during Breast Cancer Therapy

Abstract: Background. Right ventricular (RV) dysfunction during cancer therapy related cardiotoxicity and its prognostic implications have not been examined. Aim. We sought to determine the incidence and prognostic value of RV dysfunction at time of LV defined cardiotoxicity. Methods. We retrospectively identified 30 HER2+ female patients with breast cancer treated with trastuzumab (± anthracycline) who developed cardiotoxicity and had a diagnostic quality transthoracic echocardiography. LV ejection fraction (LVEF), RV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 32 publications
6
32
1
5
Order By: Relevance
“…Similar results were reported by Calleja et al, who followed 40 female patients with breast cancer treated with trastuzumab with or without anthracycline . RV FAC declined from 47% to 42% ( P = 0.01), whereas pulmonary systolic pressure significantly increased (24 ± 6.4 vs 29 ± 7.5 mm Hg, P = 0.01) …”
Section: Chemotherapy‐induced Rv Remodelingsupporting
confidence: 86%
See 4 more Smart Citations
“…Similar results were reported by Calleja et al, who followed 40 female patients with breast cancer treated with trastuzumab with or without anthracycline . RV FAC declined from 47% to 42% ( P = 0.01), whereas pulmonary systolic pressure significantly increased (24 ± 6.4 vs 29 ± 7.5 mm Hg, P = 0.01) …”
Section: Chemotherapy‐induced Rv Remodelingsupporting
confidence: 86%
“…More recently, a published study including 49 breast cancer patients undergoing anthracycline‐based chemotherapy reported that mean RV fractional area change (FAC), the important parameter of RV radial systolic function, decreased significantly from 48.3% to 42.1% ( P = 0.01) during a period of 3 months . Similar results were reported by Calleja et al, who followed 40 female patients with breast cancer treated with trastuzumab with or without anthracycline . RV FAC declined from 47% to 42% ( P = 0.01), whereas pulmonary systolic pressure significantly increased (24 ± 6.4 vs 29 ± 7.5 mm Hg, P = 0.01) …”
Section: Chemotherapy‐induced Rv Remodelingsupporting
confidence: 63%
See 3 more Smart Citations